Adaptasi Cerdas: Hubungan Investasi Digital, Kualitas Layanan, dan Peningkatan Pendapatan Hotel - Abdul Jabbar, Umar; Septa Intiar (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The hospitality sector faces major challenges, including fierce competition, low occupancy rates, and high operating costs, especially post-COVID-19 pandemic. This article examines how adaptation strategies, particularly through digital investments, affect customer satisfaction and hotel occupancy rates. This study uses a mixed method approach, combining quantitative and qualitative methods. Qualitative data was collected through in-depth interviews with managers, staff, and guests at five hotels in Semarang, Indonesia, to identify key factors for successful adaptation. Qualitative data are analyzed using MAXQDA software. Quantitative data were analyzed by multiple regression. The results show that investment priorities are a key driver of successful adaptation, although supporting factors such as improved facilities, quality of service, and the involvement of all personnel. Quantitative findings show that hotel adaptation strategies significantly affect customer satisfaction (influence of 47.10%) and occupancy rate (influence of 38.40%). Digitalization enhances operational efficiency, allowing staff to focus on personal interactions. Technologies like AI-based recommendations and mobile check-in directly improve the overall guest experience, correlating with loyalty. The conclusion of the study is that strategic digital investments, improved service quality and active staff engagement, are key to improving customer satisfaction, optimizing occupancy rates, ultimately, driving hotel revenue growth in the post-pandemic era.